Effects of working memory strategies on learning lexical collocations: the Arab context - Sneida, Taghreed I.G.; Yasir Yahya; Salina Husain (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study examines the effects of working memory strategies (WMS) on EFL Arab students learning lexical collocations. The objectives of the study are to identify the most frequent and effective WMS and to investigate how different WMS impact the learning of various lexical collocations. Eight participants took part in this study, and they were divided into two experimental groups: an L2-only English group and a code-switching group. Stimulated Recall Interviews (SRI) were used as the main methodology to investigate the participants' use of WMS. These interviews were conducted to determine the extent to which learners use WMS and, consequently, how these strategies influence their speaking abilities. The assessment process involved administering three separate speaking tests. The finding shows that repetition and imagery strategies are the most commonly used strategies and are considered to be most effective in learning collocations. Furthermore, the study demonstrates that certain types of collocations, such as adjective-noun pairings, are more accessible than others, such as those containing adverbs, in the participants' speaking performance. The implication underscores the necessity of incorporating WMS into language learning, particularly in the context of improving speaking skills. Furthermore, the study underlines the importance of mastering lexical collocations to achieve proficiency levels comparable to native speakers. This study aims to raise awareness about the practical application of WMS and the importance of collocations in language learning.